Meroditerpene pyrone, tryptoquivaline and brasiliamide derivatives from the fungus Neosartorya pseudofischeri - Paluka, Jakkapat; Kanokmedhakul, Kwanjai; Soytong, Mayamor; Soytong, Kasem; Kanokmedhakul, Somdej (My University, 2019)
Two new meroditerpene pyrones, chevalone F (1) and 11-hydroxychevalone E (2), a new tryptoquivaline analog, tryptoquivaline V (3) and a new brasiliamide analog, brasiliamide G (4), together with thirteen known compounds, chevalones A-C (5–7), chevalone E (8), 11-hydroxychevalone C (9), pyripyropene A (10), isochaetominine C (11), pyrrolobenzoxazine terpenoids CJ-12662 (12) and CJ-12663 (13), fischerindoline (14), eurochevalierine (15), 1,4-diacetyl-2,5-dibenzylpiperazine-3,7′′-oxide (16) and lecanorin (17) were isolated from the fungus Neosartorya pseudofischeri. Their structures were established on the basis of spectroscopic evidence. Compound 2 showed weak antibacterial activity against Escherichia coli and Salmonella enterica serovar Typhimurium, whereas compounds 7, 12, 13 and 15 showed antibacterial activity against Bacillus cereus and Staphylococcus aureus. In addition, compounds 13 and 14 showed cytotoxicity against KB and MCF-7 cancer cell lines, as well as the Vero cell line.
Keywords: Antibacterial; Brasiliamide; Cytotoxicity; Meroditerpene pyrone; Meroterpenoid; Neosartorya pseudofischeri; Tryptoquivaline